Game industry problems: An extensive analysis of the gray literature - Politowski, Cristiano; Petrillo, Fabio; Ullmann, Gabriel C.; Guéhéneuc, Yann-Gaël (Information and software technology, 2021)
Given its competitiveness, the video-game industry has a closed-source culture. Hence, little is known about the problems faced by game developers. However, game developers do share information about their game projects through postmortems, which describe informally what happened during the projects. The software-engineering research community and game developers would benefit from a state of the problems of the video game industry, in particular the problems faced by game developers, their evolution in time, and their root causes. This state of the practice would allow researchers and practitioners to work towards solving these problems. We analyzed 200 postmortems from 1997 to 2019, resulting in 927 problems divided into 20 types. Through our analysis, we described the overall landscape of game industry problems in the past 23 years and how these problems evolved over the years. We also give details on the most common problems, their root causes, and possible solutions. We finally discuss suggestions for future projects. We observe that (1) the game industry suffers from management and production problems in the same proportion; (2) management problems decreased over the years, giving space to business problems, while production problems remained constant; (3a) technical and game design problems are decreasing over the years, the latter only after the last decade; (3b) problems related to the team increase over the last decade; (3c) marketing problems are the ones that had the biggest increase over the 23 years compared to other problem types; (4) finally, the majority of the main root causes are related to people, not technologies. Conclusions: In this paper, we provide a state of the practice for researchers to understand and study video-game development problems. We also offer suggestions to help practitioners to avoid the most common problems in future projects.